Longevity of seeds and soil seed bank of the Cerrado tree Miconia chartacea (Melastomataceae) - Escobar E., Diego F. [UNESP]; Cardoso, Victor J. M. [UNESP] (My University, 2015)
Miconia chartacea is a widely distributed tree in Brazil, occurring at altitudes ranging from 300 m to 1900 m in the Caatinga, Cerrado and Atlantic Forest biomes. In this work we attempted to classify M. chartacea seeds regarding their behaviour during storage and their germination syndrome and to determine, from a storage test in Cerrado soil and laboratory conditions in situ and ex situ, the longevity of seeds, as well as the capacity of the species to form a soil seed bank. The results suggested that M. chartacea seeds form a transient soil seed bank in the Cerrado and can be classified as orthodox in terms of storage behaviour, although the seeds are dispersed with a relatively high water content. The life span of seeds was favoured in soil-stored seeds in comparison with dry storage at 25°C, whereas storage at low temperatures prevented a decrease of the seed's germinability with storage time (330 d). M. chartacea seeds are dispersed during the dry season and germinate during the next rainy season, which can be classified as an intermediate-dry germination syndrome. Seeds of this species are dispersed in the Cerrado when temperatures and soil moisture are relatively low, which favours the formation of a soil seed bank, considering that the seeds tolerate desiccation and their longevity is favoured by low temperatures. A transient seed bank type is favoured by the loss of viability in storage at warm temperatures linked to the rainy season, and the predictable seasonal variations in climate in the region, with germination being restricted to the beginning of the rainy season.
Keywords: Brazilian savanna; germinability; germination rate; germination syndrome; seed storage; viability